Design and MATLAB Simulation of Pitch Motion System Controller for Underwater Vehicle - Che Ku Amran, Che Ku Hariz (IRC, 2017)
Underwater vehicle is an important machine nowadays. It can perform multiple underwater complex tasks. For example, pipelines detection or mapping, underwater terrain exploration and underwater inspections. Due to rotation of the thruster at back of most underwater vehicle, it causes disturbances of fluid around the vehicle and affect the stability of the vehicle. Thus, a control system for the motion of the vehicle should be designed to compensate the instability. However, in this project the focus is directed to design a PID controller for one degree of vehicle’s motion which is pitch motion. The study is based on NPS AUV II which is an underwater vehicle. Recently, there are many researches related to underwater vehicle’s motion controller.